Metabolic cardio- and reno-protective effects of empagliflozin in a prediabetic rat model - Huttl, M; Markova, I; Miklankova, D; Oliyarnyk, O; Trnovska, J; Kucera, J; Sedlacek, R; Haluzik, M; Malinska, H (Journal of physiology and pharmacology, 2020)
The mechanisms behind the cardiovascular and renal benefits of empagliflozin is not fully understood. The positive impact of the medication on cardiovascular mortality can not be solely attributed to its antidiabetic effect, with a metabolic mechanism possibly involved. To investigate the metabolic effects of empagliflozin treatment (10 mg/kg/day for 6 weeks), we used an adult male rat model with serious vascular complications associated with metabolic syndrome and prediabetes. Impaired glucose tolerance, severe albuminuria and impaired insulin sensitivity were induced by intragastric administration of methylglyoxal and high sucrose diet feeding for four months. Although empagliflozin decreased body weight, non-fasting glucose and insulin, glucagon levels remained unchanged. In addition, empagliflozin increased adiponectin levels (+40%; p < 0.01) and improved skeletal muscle insulin sensitivity. Increased non-esterified fatty acids (NEFA) in empagliflozin-treated rats is understood to generate ketone bodies. Empagliflozin increased β-hydroxybutyrate levels in serum (+66%; p < 0.05) and the myocardium (30%; p < 0.01), suggesting its possible involvement as an alternative substrate for metabolism. Empagliflozin switched substrate utilisation in the myocardium, diverting glucose oxidation to fatty acid oxidation. Representing another favorable effect, empagliflozin also contributed to decreased uric acid plasma levels (-19%; p < 0.05). In the kidney cortex, empagliflozin improved oxidative and dicarbonyl stress parameters and increased gene expression of β-hydroxybutyrate dehydrogenase, an enzyme involved in ketone body utilisation. In addition, empagliflozin decreased microalbuminuria (-27%; p < 0.01) and urinary neutrophil gelatinase-associated lipocalin (NGAL) excretion (-29%; p < 0.01). Our results reveal the important systemic metabolic effect of empagliflozin on alterations in substrate utilisation and on increased ketone body use in prediabetic rats. Improved oxidative and dicarbonyl stress and decreased uric acid are also possibly involved in the cardio- and reno-protective effects of empagliflozin.
Keywords: glukosidy; glukosa; Glucosides; Rats; Benzhydryl Compounds; ochranné látky; prediabetes; benzhydrylové sloučeniny; ketolátky; Disease Models, Animal; Rats, Wistar; mužské pohlaví; Oxidative Stress; krysa rodu Rattus; modely nemocí na zvířatech; zvířata; Protective Agents; ledviny; Heart; Ketone Bodies; Prediabetic State; potkani Wistar; Kidney; oxidační stres; inzulinová rezistence; Insulin Resistance; srdce; Glucose; Male; Animals